The tainted spotlight - How crisis overshadowed Brazil’s public diplomacy bet in hosting sports events and led to a downgrade of the reputation of the country - Buarque, Daniel Sousa (Revista Trama Interdisciplinar, 2018)
While Brazil was experiencing a rise in its international political and economic profile, with increased visibility and recognition, the country acquired the right to host two of the biggest global events in the international agenda, the 2014 World Cup and the 2016 Summer Olympic Games. This was part of a long-term public diplomacy strategy to attract the international spotlight, hold the world’s attention and showcase a developing modern country, a means to increase its soft power (Buarque, 2015; Soares e Castro, 2013). It was also part of a historic ambition of the country to become a Great Power of the world through the development of its soft power (Mares and Trinkunas, 2016). However, a series of internal crises took over the country and instability ensued, so bad news overshadowed the successful organization of the events, and instead of improving the reputation of Brazil, the image of the country only worsened. Although there is no consensus even on the definition of “nation image” and on a methodology to measure its multidimensional character, this article analyses seven different indexes that propose to do that, through surveys, interviews and analysis of public data. According to these different studies, the global perception of Brazil changed for the worse in the four years between 2013, before the World Cup, and 2017, after the Olympic Games. This means that the plan did not go as the country had hoped, and the strategy of using visibility to further develop the country’s soft power backfired, which seems to repeat a pattern in the history of Brazil, a country where political and economic instabilities take over from time to time, affecting its international ambition (Mares and Trinkunas, 2016).